“‘The Left Turn’ in Mexico is a new phenomenon” - A. N. Borovkov (Ибероамериканские тетради)
Interview with Anatoliy Nikitovich Borovkov, Doctor of Political Science, Leading Researcher of the Institute of Latin America of the Russian Academy of Sciences, Editor-in-Chief of the Iberoamérica journal. From 1969 to the present date, Dr. Borovkov works at the Institute of Latin America of the Russian Academy of Sciences. He is the author of more than 100 research publications. From 1984 to 1994, he was a representative of the Institute of Latin America and a regional correspondent for the Latin America magazine in Mexico and Central America. Dr. Borovkov is a prominent Russian researcher specializing on Mexico; his research interests include analysis of political parties, electoral legislation processes in Mexico, the socio-economic situation in this country and its relations with the United States.The interview was conducted by: A.A. Habarta.